The Influence of Narrative Method through Employing Enrichment, Interactive, Multimedia Materials on the Enhancement of Reading Comprehension Skills in Arabic Language among Second Grade Students - Al-Saraj, Rowaida Harbi Mohammad; Dyab Hamadneh , Adeeb (Dirasat: Educational Sciences, 2022)
Objectives:The current study is to investigate the effect the storytelling method by employing Arabic among students of the second garde using the quasi-experimental approach and interactive multimedia enrichment materials were formed in developing reading comprehension skills in language. Methods: The study sample consisted of (62) students from jabal Prince Faisal Basic School. The sample was divided randomalu into two groups, one of which is experimental and included (31) male and female students and the other is a control and it had (31) male and female students. The study was applied in the first semester of the academic year 2020/2021 and the study tool was prepared from it by examining the literal comprehension of the realable and in its final form of (10) paragraphs, and it was applied after verification of validity and consistency. Results: The result of the study indicated that there were statistically significant differences in the arithmetic averages and orbital deviations of the students, performance on the test of the literal comprehension of the post- reading in favor of the experimental group that studied using the method of storytelling by employing the media and light of these results. Conclusions: The study recommended the necessity of employing multimedia And storytelling to restore the Arabic language.